Vinpocetine alleviated alveolar epithelial cells injury in experimental pulmonary fibrosis by targeting PPAR-γ/NLRP3/NF-κB and TGF-β1/Smad2/3 pathways - Zeena A. Hussein; Ahmed R. Abu-Raghif; Nibras J. Tahseen; Khalid A. Rashed; Nada S. Shaker; Hayder Adnan Fawzi (Scientific Reports, 2024)
Abstract This study aimed to investigate the potential anti-fibrotic activity of vinpocetine in an experimental model of pulmonary fibrosis by bleomycin and in the MRC-5 cell line. Pulmonary fibrosis was induced in BALB/c mice by oropharyngeal aspiration of a single dose of bleomycin (5 mg/kg). The remaining induced animals received a daily dose of pirfenidone (as a standard anti-fibrotic drug) (300 mg/kg/PO) and vinpocetine (20 mg/kg/PO) on day 7 of the induction till the end of the experiment (day 21). The results of the experiment revealed that vinpocetine managed to alleviate the fibrotic endpoints by statistically improving (P ≤ 0.05) the weight index, histopathological score, reduced expression of fibrotic-related proteins in immune-stained lung sections, as well as fibrotic markers measured in serum samples. It also alleviated tissue levels of oxidative stress and inflammatory and pro-fibrotic mediators significantly elevated in bleomycin-only induced animals (P ≤ 0.05). Vinpocetine managed to express a remarkable attenuating effect in pulmonary fibrosis both in vivo and in vitro either directly by interfering with the classical TGF-β1/Smad2/3 signaling pathway or indirectly by upregulating the expression of Nrf2 enhancing the antioxidant system, activating PPAR-γ and downregulating the NLRP3/NF-κB pathway making it a candidate for further clinical investigation in cases of pulmonary fibrosis.